Hubungan Kecerdasan Emosional Siswa dengan Hasil Belajar PAI Kelas VIII MTs Thoriqul Huda Catakgayam Selatan Mojowarno Jombang - Abdul Rouf; Abu Yasa (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2019)
This research is motivated by the phenomenon that to achieve high achievement in learning, one must have a high intelligence quotient (IQ), because intelligence is a potential provision that will facilitate learning and in turn will produce optimal learning achievement. In fact, in the learning process of students, not only IQ is needed. IQ cannot function properly without emotional appreciation of the subjects delivered at school. This study aims to find out whether there is a relationship between emotional intelligence and learning outcomes of class VIII PAI MTs Thoriqul Huda South Catakgayam Mojowarno Jombang. The sampling technique uses sample random sampling. Data collection techniques to measure students' emotional intelligence are carried out by distributing questionnaires, while measuring student learning outcomes is done by asking students for the grades in the MTs. The data analysis technique used in this study is the product moment correlation data analysis. The results of this study can be concluded that there is a relationship between emotional intelligence and learning outcomes of PAI at MTs Thoriqul Huda South Catakgayam Mojowarno Jombang.